Zilucoplan, a macrocyclic peptide inhibitor of human complement component 5, uses a dual mode of action to prevent terminal complement pathway activation - Tang, Guo-Qing; Tang, Yalan; Dhamnaskar, Ketki; Hoarty, Michelle D.; Vyasamneni, Rohit; Vadysirisack, Douangsone D.; Ma, Zhong; Zhu, Nanqun; Wang, Jian-Guo; Bu, Charlie; Cong, Bestine; Palmer, Elizabeth; et al. (Frontiers in Immunology, 2023)
Introduction: The complement system is a key component of the innate immune system, and its aberrant activation underlies the pathophysiology of various diseases. Zilucoplan is a macrocyclic peptide that binds and inhibits the cleavage/activation of human complement component 5 (C5). We present in vitro and ex vivo data on the mechanism of action of zilucoplan for the inhibition of C5 activation, including two clinically relevant C5 polymorphisms at R885. Methods: The interaction of zilucoplan with C5, including for clinical C5 R885 variants, was investigated using surface plasmon resonance (SPR), hemolysis assays and ELISA. The interference of C5b6 formation by zilucoplan was investigated by native gel analysis and hemolysis assay. The permeability of zilucoplan in a reconstituted basement membrane was assessed by the partition of zilucoplan on Matrigel-coated transwell chambers. Results: Zilucoplan specifically bound human complement C5 with high affinity, competitively inhibited the binding of C5 to C3b, blocked C5 cleavage by C5 convertases and the assembly of the cytolytic membrane attack complex (MAC, or C5b9). Zilucoplan fully prevented the in vitro activation of C5 clinical variants at R885 that have been previously reported to respond poorly to eculizumab treatment. Zilucoplan was further demonstrated to interfere with the formation of C5b6 and inhibit RBC hemolysis induced by plasmin-mediated non-canonical C5 activation. Zilucoplan demonstrated greater permeability than a monoclonal C5 antibody in a reconstituted basement membrane model, providing a rationale for the rapid onset of action of zilucoplan observed in clinical studies. Conclusion: Our findings demonstrate that zilucoplan uses a dual mode of action to potently inhibit the activation of C5 and terminal complement pathway including wild-type and clinical R885 variants that do not respond to eculizumab treatment. These data may be relevant to the clinically demonstrated benefits of zilucoplan.